Cognitive-impairment-free life expectancy (CIFLE) among older adults in India: A gender and residence based study - Madhurima Sharma; Abdul Fathah; Indrajit Goswami (Archives of Gerontology and Geriatrics Plus, 2025)
Background: While cognitive impairment (CI) and dementia are among the most severe morbid conditions in later life, life expectancies free from CI have been much less investigated than measures of physical functioning. This study aimed to determine the health expectancies in middle aged and older adults in India, considering cognitive status as a health indicator. Methods: We estimated Cognitive Impairment-free life expectancy (CIFLE) in India for people aged 45 and older using data from Longitudinal Ageing Study in India (LASI), 2017-18. Mortality data has been derived from the Sample Registration System (SRS), 2016-20. Sullivan’s method is used to estimate the average number of years a person can expect to live with and without cognitive impairment. Results: The prevalence of CI among Indian adults 45 and above is 10.28 %, increasing from 4.34 % (45–49) to 47 % (85+). Higher rates in females (13.65 % vs 6.42 % in males) and rural areas (12.39 % vs 6.38 % urban). The results indicate that after attaining age 60, males are expected to live 15 more years as cognitive impairment-free, which is only 12 years for females; though life expectancy for females is higher than that of males. Older adults in rural areas are expected to have fewer cognitive impairment-free years than in urban areas. Conclusion: Longer life does not extend cognitive health. CI reduces quality of life and increases care needs, aligning with global trends. The disparities in CI-free life expectancy between genders and rural-urban areas highlight the need for targeted interventions and policies to address cognitive health inequalities in India.